Development of Digital Module "History of South Tapanuli during the Indonesian Independence Revolution" Based on Local Heroic Values for History Learning in Senior High Schools in Padangsidimpuan City - Burhanuddin Burhanuddin; Bincar Nasution (International Journal of Community Service (IJCS), 2025)
The integration of digital learning modules in history education presents significant opportunities for enhancing student engagement and fostering character development through local heroic narratives. This study aimed to develop a comprehensive digital module titled "History of South Tapanuli during the Indonesian Independence Revolution" grounded in local heroic values for implementation in senior high schools across Padangsidimpuan City. Employing a qualitative research methodology, the study involved semi-structured interviews (n=24) with history teachers and educational stakeholders, focus group discussions (n=4 groups, 32 participants) with secondary school students, and document analysis of curricular materials and local historical records. Data were analyzed through thematic coding and content analysis, revealing three primary themes: integration of local heroic values in curriculum design, pedagogical effectiveness of digital modules, and barriers to implementation. Findings indicate that the digital module effectively contextualizes national independence history within local South Tapanuli narratives, particularly through the portrayal of regional heroes such as Commissioner Police Mas Kadiran and the East Sumatra Social Revolution participants. The module demonstrates significant potential in cultivating student awareness of regional contributions to national independence, enhancing critical thinking skills, and fostering nationalistic sentiment grounded in local heroic exemplars. However, implementation requires addressing infrastructure limitations, teacher digital literacy development, and curriculum alignment. This research provides empirical evidence supporting the efficacy of locally-grounded digital learning modules in enhancing history education quality while promoting character formation based on authentic regional heroic values in the Indonesian educational context.